Developing Digital Marketing On Getuk Nyimut MSMEs - Marka, Mira Meilia; Prasetyaningrum, Indah Dwi; Subono, Agung; Sumekar, Kertati; Robiyanto, Febra; Maharani, Indah Puspita (Universitas Sahid Surakarta, 2023)
Community service activities with Getuk Nyimut MSMEs aim to increase competitive advantage. Getuk nyimut is a food that has become an icon for visitors at the Muria Mountains. Getuk nyimut products are starting to develop along with the increasing number of consumers from outside the region who visit Kajar Village. This results in high competition for getuk nyimut. Business people compete to market their products to consumers through various strategies to stay and winning the competition. Based on the problems faced by partners, the team made efforts to improve business management through improving marketing and financial aspects. The solution given to partners is expanding market share through digital marketing as a means of product promotion media. Online promotion is carried out through social media such as Instagram and TikTok. Beside that, using product labels on packaging can increase product awareness so the products can be known to the more consumers. The solution to problems in the financial aspect is training and assistance in recording business finances by carrying out periodic recaps of business income and expenses. These efforts can indicate business progress because partners can find out his profits and losses. Partners utilize the Siapik application to record cash flow so these activities can be carried out efficiently. Keywords: MSMEs, Getuk Nyimut, Marketing, Finance